Respuestas
Respuesta dada por:
8
Respuesta:
todo junto = -82944
(-6)×(-6)×(-6)×(-6)= 1296
(-4)×(-4)×(-4)= -64
marioortegaher:
gracias pive
Respuesta dada por:
5
- (−6)⋅(−6)⋅(−6)⋅(−6)=1296
- (-4)×(-4)×(-4)=-64 Explicación paso a paso: (−6)⋅(−6)⋅(−6)⋅(−6) Multiplica −6 y −6 para obtener 36. 36(−6)(−6) Multiplica 36 y −6 para obtener −216. −216(−6) Multiplica −216 y −6 para obtener 1296. 1296
- −4⋅−4⋅−4 Multiplica −4 y −4 para obtener 16. 16(−4) Multiplica 16 y −4 para obtener −64. −64
Preguntas similares
hace 2 años
hace 2 años
hace 5 años
hace 5 años
hace 5 años
hace 7 años